The Narratives of Local Women’s Resilience in Disaster and Climate Change: The Voices of Indonesian Women in the Watershed Areas - Hendrastiti, Titiek Kartika; Kusujiarti, Siti; Sasongko, Rambat Nur (UI Scholars Hub, 2023)
This study analyzes the narratives of women’s resilience in disaster from the post-colonial feminism approach. Ecological justice and gender issues have been addressed by other studies on Indonesia to amplify the voices of Indonesian women, but few of them focus on women’s narratives. As a culture relying on oral traditions, Indonesian women’s narratives and stories are instrumental in decolonizing the knowledge on ecological justice. Even though feminist perspectives play an instrumental role in addressing ecological justice in Indonesia, studies using post-colonial feminism remain very limited. This study employs post-colonial feminist ethnography and focuses on three watershed areas in Bengkulu, Indonesia: Rindu Hati village representing rural upstream location; Talang Empat village representing rural midstream region, and Tanjung Jaya village representing downstream urban areas. Interviews were conducted with women who are members of peasant groups, agricultural workers, traders, village administrators, and other community members. The narratives show several important trends: (a) Women’s daily live reflects their knowledge about the environment and women’s responses to disaster and climate change indicating local eco-consciousness, resilience, and adaptation to changes. (b) Local power configuration contributes to resilience. There are interconnections of gender relations, disaster resilience, and environmental sustainability. Local power map shows the interconnection between disaster responses, environmental sustainability and gender relations in the community. (c) Upstream population tends to have higher commitment to environmental conservation and disaster resilience compared to the communities in the midstream and downstream locations. Women’s position in the circle of power in watershed management has important influence in their resilience facing disaster and climate change. These narratives inform the interrelations of women’s positions, disaster resilience, and eco-consciousness in creating ecological justice.